Bamboo diversity of Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2018)
Ervianti D, Widjaja EA, Sedayu A. 2019. Bamboo diversity of Sulawesi, Indonesia. Biodiversitas 20: 91-109. Bamboo is one of the important plants in the world. Beside their economic important, bamboo also plays an important role in the environment for climate change. The purpose of this study was to inventory the bamboo diversity in Sulawesi. The methodology used in this study is by observing herbarium specimens kept in the Herbarium Bogoriense (BO) and field experience by the second author (EAW). The result showed that there are 39 species of 12 genera in Sulawesi, i.e. Bambusa blumeana, B. glaucophylla, B. maculata, B. multiplex, B. tuldoides, B. vulgaris, Chloothamnus sp., Dendrocalamus asper, Dinochloa albociliata, D. aopaensis, D. barbata D. cordata, D. erecta, D. hirsuta, D. morowaliensis, D. petasiensis, D. pubiramea , D. truncata, Dinochloa sp.1, Dinochloa sp.2, Dinochloa sp.3, Dinochloa sp.4, Dinochloa sp.5, Dinochloa sp.6, Dinochloa sp.7, Dinochloa sp.8, Dinochloa sp.9, Fimbribambusa sp., Gigantochloa apus, G. atroviolacea, G. atter, Neololeba atra, Phyllostachys aurea, Racemobambos celebica, Schizostachyum brachycladum, S. latifolium, S. lima, Sphaerobambos subtilis, and Thyrsostachys siamensis. Identification keys and descriptions are presented. This data reported will be used as basic information for bamboo conservation and bamboo industry.
Keywords: Bamboo; description; diversity; identification key; Sulawesi